Developing Students' Speaking Performance Through Cooperative Learning Method - Amin, Fatimah Hidayahni (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
The major problems of this study were how to develop the students’ speaking performance in terms of speaking accuracy dealing with acceptable pronunciation, correct grammar, and appropriate word choice and how to trigger the students’ positive attitudes toward the use of cooperative learning method in terms of Students Team Achievement Division method. The results of the study showed that (1) the students’ speaking performance in terms of speaking accuracy dealing with acceptable pronunciation, correct grammar, and appropriate word choice developed significantly indicated by the significant differences between the mean scores of pre and post tests at the 0.05 level for each component, and (2) the use of Students Team Achievement Division as one of the cooperative learning methods could trigger the students’ positive attitudes. The study concluded that the use of Students Team Achievement Division as the teaching method has brought new nuance in English language teaching and become a need in an attempt of developing the students’ speaking performance in terms of speaking accuracy and triggering their positive attitude to speak English.Keywords: Speaking Performance, Cooperative Learning